The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10815-014-0246-8
|View full text |Cite
|
Sign up to set email alerts
|

Basal serum testosterone levels correlate with ovarian response but do not predict pregnancy outcome in non-PCOS women undergoing IVF

Abstract: Purpose To evaluate basal testosterone (T) levels in women undergoing in vitro fertilization (IVF) cycles and examine the association between basal T levels and ovarian response or IVF pregnancy outcome. Methods We retrospectively analyzed 1413 infertile Chinese women undergoing their first IVF treatment at our institution's reproductive center from March 2011 to May 2013. The basal testosterone (T) levels in women undergoing in vitro fertilization (IVF) and the relationship between basal T levels and ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…According to their article, PCOS had a different response to stimulation in a wide range, and to the best of knowledge, different phenotypes were not assessed separately. The effect of basal testosterone levels in IVF cycles of patients without PCOS was evaluated in a study by Sun et al ( 22 ) consistent with our results in PCOS patients, the authors concluded that although basal testosterone did not predict pregnancy outcomes, it was associated with the large follicles on human koryonik gonadotropin day, FSH dosage, and also that lower levels of basal testosterone might be related with poor ovarian response ( 22 ) . Embryo cleavage kinetics were studied by Wissing et al ( 23 ) with a small sample size.…”
Section: Discussionsupporting
confidence: 83%
“…According to their article, PCOS had a different response to stimulation in a wide range, and to the best of knowledge, different phenotypes were not assessed separately. The effect of basal testosterone levels in IVF cycles of patients without PCOS was evaluated in a study by Sun et al ( 22 ) consistent with our results in PCOS patients, the authors concluded that although basal testosterone did not predict pregnancy outcomes, it was associated with the large follicles on human koryonik gonadotropin day, FSH dosage, and also that lower levels of basal testosterone might be related with poor ovarian response ( 22 ) . Embryo cleavage kinetics were studied by Wissing et al ( 23 ) with a small sample size.…”
Section: Discussionsupporting
confidence: 83%
“…In normal cycling women, there is a positive correlation between free androgen index and total ovarian follicle count following ovarian hyperstimulation (Dickerson et al 2010). Similarly, serum testosterone levels have been described to positively correlate with ovarian response (Barbieri et al 2005, Sun et al 2014, Xiao et al 2016 and pregnancy outcomes (Frattarelli & Peterson 2004, Lu et al 2014 in IVF, inferring that a lower level of testosterone may relate with a poorer ovarian response (Sun et al 2014, Xiao et al 2016 and a decreased success in achieving a pregnancy. However, studies often do not report a consistent correlation between serum androgen levels and IVF reproductive outcomes (Lu et al 2014, Sun et al 2014, Xiao et al 2016.…”
Section: Clinical Evidence Indicating the Need For Optimized Androgenmentioning
confidence: 99%
“…Serum T levels have been suggested to be positively associated with ovarian response 43 , 44 and even pregnancy outcomes 44 , 45 in women undergoing IVF cycles. Although some conflicting studies have shown that serum T levels do not predict IVF outcomes 43 , 46 , available data have indicated that T supplementation may improve ovarian response and IVF outcomes in PORs 47 , 48 . In a randomized controlled trial of 110 PORs undergoing IVF cycles, Kim et al reported that pretreatment with transdermal T gel significantly increased AFC and reduced the day of stimulation and total dosage of gonadotropins.…”
Section: Discussionmentioning
confidence: 99%